Young children's creative thinking - Fumoto, Hiroko; Sage eBooks (Los Angeles, [Calif.] ; London : SAGE, 2012)
In this text the authors push forward our understanding of what young children's creative thinking is, and how it promotes young children's well-being.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Early childhood education; Creative thinking in children; Electronic books